2007
DOI: 10.1007/s10750-006-0470-z
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent individual growth of marble trout (Salmo marmoratus) in the Soca and Idrijca river basins, Slovenia

Abstract: Although the main features of salmonid life cycles are currently well known, marble trout (Salmo marmoratus) populations have been scarcely studied due to the present limited geographical distribution of the species. In this work we tested the hypothesis of density-dependent individual growth of marble trout with data gathered from multi-year on-going monitoring started in 1996 in three streams (Zakojska, Gorska and Gatsnik) in the Soca and Idrijca river basins (Slovenia). As observed for other salmonid specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Two of the stocks developed clear bimodal length-frequency distributions, whereas the other two stocks displayed skewed or weakly bimodal length-frequency distributions. Vincenzi et al (2007b) did not observe polymodality in the length-frequency distribution of marble trout, and our analysis suggests that episodes of massive mortality may contribute to the observed pattern, since all marble trout populations living in Slovenian streams are impacted by flood events. We predict that in populations which are adapted to stream environments that are not subject to flood events, multi-modality of the length-frequency distribution may be observed.…”
Section: Discussionsupporting
confidence: 42%
“…Two of the stocks developed clear bimodal length-frequency distributions, whereas the other two stocks displayed skewed or weakly bimodal length-frequency distributions. Vincenzi et al (2007b) did not observe polymodality in the length-frequency distribution of marble trout, and our analysis suggests that episodes of massive mortality may contribute to the observed pattern, since all marble trout populations living in Slovenian streams are impacted by flood events. We predict that in populations which are adapted to stream environments that are not subject to flood events, multi-modality of the length-frequency distribution may be observed.…”
Section: Discussionsupporting
confidence: 42%
“…age-specific survival, body-size growth rates and the relationship between female length and fecundity (Vincenzi et al 2007a(Vincenzi et al , b, 2008. We also observed density-dependent patterns in marble trout for both individual growth (Vincenzi et al 2007b) and firstyear survival (Vincenzi et al 2007a). Here, we report our individual-based model of marble trout population dynamics which we developed based on marble trout population parameters and empirical models of densitydependent processes (Vincenzi et al 2007a(Vincenzi et al , b, 2008.…”
Section: Introductionmentioning
confidence: 52%
“…is the maximum length (mm), k is the Brody's growth coefficient relating age to length and x 0 (years) is the age at which length equals 0. The growth curve parameters for both Gorska and Zakojska marble trout populations were estimated separately by pooling together age-length data from different years (Vincenzi et al 2007b) (Table 1). However, Vincenzi et al (2007b) found evidence of density-dependent individual growth in the newly introduced marble trout populations.…”
Section: Density-dependent Individual Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a 10-fold decrease in population density, either through reduced stocking density or increased loss (the slope estimates are nearly identical), is predicted to yield a twofold increase in mean body mass. Using a large-scale manipulation in natural streams enabled this closer look at the drivers underlying the extreme spatial variation in juvenile Atlantic salmon growth in the field, expanding beyond previous observational (Crisp 1993;Newman 1993;Imre et al 2005;Lobon-Cervia 2007;Vincenzi et al 2007) and experimental (Jenkins et al 1999;Bohlin et al 2002;Einum et al 2006) studies reporting densitydependent growth of salmon and trout in natural streams. Here, we review the potential limitations of this result and implications for Atlantic salmon populations and stream fisheries management.…”
Section: Discussionmentioning
confidence: 99%